The effect of diabetes on the connective tissue and the bone-joint system - Chwalba, Artur; Otto-Buczkowska, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Diabetes is associated with a number of complications, including renal disease, peripheral neuropathy, retinopathy, and vascular events. Aim. Article presents the research results reported in the scientific literature about the influence of diabetes on connective tissue and the bone-joint system. Material and methods. Analysis of literature. Conclusion. Due to its multi-systemic nature, the development of additional manifestations, such as musculoskeletal complications, is possible including, for example diabetic osteopathy, limited joint mobility, joint disorders, and other, many of which are subclinical and correlated with the disease duration and its inadequate control. They should be recognized and treated properly, because their management improves the patients’ quality of life.
Keywords: diabetes mellitus; diabetic osteopathy; limited joint mobility; joint disorders